Letramento em saúde e a influência da linguagem nas práticas médicas: percepção dos estudantes de medicina de universidades públicas de Belém do Pará - ASSIS, Alexa Camila Lopes de (2024)
Health Literacy refers to an individual's ability to acquire, process and comprehend health related information. Inadequate literacy can lead to increased patient morbidity. However, this topic is not widely disseminated in health sciences courses, which may result in undervaluing the importance of adapted communication in proper patient care. Therefore, this present monograph aims to "assess the perception of medical students from public colleges in Belém do Pará regarding the theme 'Health Literacy' and how this knowledge impacts their education." This is a descriptive cross-sectional quantitative study conducted at two medical colleges in Belém do Pará, Universidade Federal do Pará, and Universidade Estadual do Pará. The sample included 723 students enrolled from September to December 2022, and data were collected through questionnaires. The analysis was performed using Microsoft Excel and Bioestat 5.4, applying the Chi-square and G-test (α=5%, p ≤ 0.05%). It was found that socioeconomic data and the student's college of origin do not have a significant relationship with knowledge about Health Literacy. In some questions, there were differences between the basic, clinical, and internship cycles concerning the explanation of colloquial terminologies (p < 0.0001), difficulties in establishing doctor-patient relationships (p = 0.0379), prescribing for elementary school patients (p = 0.0008) and high school patients (0.0003), discussions about more comprehensible prescriptions in the educational curriculum (p < 0.0001), and lower risk of morbidity and mortality with Health Literacy (p = 0.0182). Additionally, students who are familiar with the concept of Health Literacy identify more tests that assess patient literacy (p = 0.0011); however, knowledge of the concept and the tests is low (15.49% and 4%, respectively). Moreover, the level of difficulty in establishing medical treatment increases with lower levels of patient education (p < 0.0001). In light of these findings, the subject is not adequately disseminated in the researched universities, both in the curricular and extracurricular contexts, and the majority of students are not familiar with the concept and characteristics of Health Literacy. More attention and research on the subject are urgently needed.